18th Prof. Vladas Gronskas International Scientific Conference: Abstract Book - Krikščiūnienė, Dalia; Šarkiūnaitė, Ingrida (Vilnius University Proceedings, 2024)
The conference “18th Prof. Vladas Gronskas International Scientific Conference” is an arena for cooperation and scholarly fellowship, with young researchers, bachelor, master and doctoral students from Lithuania and foreign countries. It is an arena for open discussion where young researches have the opportunity to present and share their scientific insights. This conference encourages internationalization and a closer cooperation between science and business. The conference keynote speakers – business representatives – provide participants with new insights and inspiration for further research. The main goal of this scientific gathering is to contribute to the reliable, safe, effective and sustainable economy and business development. Encouraging entrepreneurship is a crucial condition for economic growth and this puts forward a new approach to business, creativity, value creation, and the implementation of innovations. It is precisely in this context where business and science should interact.